Trinidad and Tobago primary education program (77-0031): Project report - Inter-American Development Bank (IDB, 1986)
The objective of this programme was to improve the quality of primary education and, thus, provide a sound basis for attainment of universal and good quality secondary education. A Learning Resource Centre was established to provide a permanent means of developing, updating, and introducing innovations in the education system. Other activities of the programme which are identified include the provision of school libraries or library facilities in all primary schools, and stocking them with an average of 11-12 new reference or textbooks per student
Keywords: Project reports